2015
DOI: 10.1021/es504882f
|View full text |Cite
|
Sign up to set email alerts
|

Facultative Nitrate Reduction by Electrode-Respiring Geobacter metallireducens Biofilms as a Competitive Reaction to Electrode Reduction in a Bioelectrochemical System

Abstract: Alternative metabolic options of exoelectrogenic biofilms in bioelectrochemical systems (BESs) are important not only to explain the fundamental ecology and performance of these systems but also to develop reliable integrated nutrient removal strategies in BESs, which potentially involve substrates or intermediates that support/induce those alternative metabolisms. This research focused on dissimilatory nitrate reduction as an alternative metabolism to dissimilatory anode reduction. Using the exoelectrogenic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…The predicted Nitrospirales–Geobacteraceae association might reflect a cross-feeding relationship, where Geobacteraceae species use nitrate generated by Nitrospirales members as electron acceptor. Although Geobacteraceae are better known as metal reducers, several Geobacteraceae species are able to grow on nitrate as the sole electron acceptor ( Kashefi et al, 2003 ; Kashima and Regan, 2015 ). Since Geobacteraceae species are anaerob and several members of Nitrospirales aerob, their interaction may take place indirectly via nitrate diffusing into deeper soil layers.…”
Section: Resultsmentioning
confidence: 99%
“…The predicted Nitrospirales–Geobacteraceae association might reflect a cross-feeding relationship, where Geobacteraceae species use nitrate generated by Nitrospirales members as electron acceptor. Although Geobacteraceae are better known as metal reducers, several Geobacteraceae species are able to grow on nitrate as the sole electron acceptor ( Kashefi et al, 2003 ; Kashima and Regan, 2015 ). Since Geobacteraceae species are anaerob and several members of Nitrospirales aerob, their interaction may take place indirectly via nitrate diffusing into deeper soil layers.…”
Section: Resultsmentioning
confidence: 99%
“…Several species of Geobacter have been shown to reduce nitrates. [30][31][32] Geobacter sulfurreducens has been electrochemically studied as a biofilm 18,19,33 as well as immobilized on carbon electrodes by pectin, 20 where DET still occurred when the G. sulfurreducens were immobilized on the electrode without forming a biofilm.…”
Section: F652mentioning
confidence: 99%
“…To date, the effect of nitrate on electricity generation by exoelectrogens has not been determined. Few studies have reported that denitrifying exoelectrogens conduct denitrification as a facultative metabolism in bioelectrochemical systems (BESs) (Xing et al, 2010 ; Fu et al, 2013 ; Kashima and Regan, 2015 ). The power output of MFCs with Comamonas denitrificans (Xing et al, 2010 ) or Calditerrivibrio nitroreducens (Fu et al, 2013 ) was found to be decreased when nitrate was added to the anode chamber of MFCs, suggesting that the change in metabolic pathway affected the electricity performance negatively.…”
Section: Introductionmentioning
confidence: 99%
“…The power output of MFCs with Comamonas denitrificans (Xing et al, 2010 ) or Calditerrivibrio nitroreducens (Fu et al, 2013 ) was found to be decreased when nitrate was added to the anode chamber of MFCs, suggesting that the change in metabolic pathway affected the electricity performance negatively. Kashima and Regan ( 2015 ) subsequently reported that anodic denitrification and anode respiration shifted rapidly according to nitrate concentration in a BES inoculated with the anode-respiring bacterium Geobacter metallireducens , and that the current output of an MFC was strongly inhibited when the nitrate concentration was above the critical level (0–56 mg N L −1 ). The critical nitrate concentrations have a significant relationship with the biofilm protein concentrations of anode biofilms, without being appreciably impacted by the anode potential.…”
Section: Introductionmentioning
confidence: 99%